Farm size and productivity growth in the United States Corn Belt. (April 2019) - Key, Nigel
Highlights: Total factor productivity increases with crop farm size in the U.S. Corn Belt. Farms harvesting less than 100 acres lagged in productivity growth from 1982 to 2012. Crop farm consolidation accounted for one sixth of aggregate productivity growth. Abstract: In recent decades, agricultural production in the U.S. has continued to shift to large-scale operations, raising concerns about the economic viability of small and midsized farms. To understand whether economies of size provided an incentive for the consolidation of production, the study estimates the total factor productivity (TFP) of five size classes of grain-producing farms in the U.S. Heartland (Corn Belt) region. Using quinquennial Agricultural Census data from 1982 to 2012 the study also compares TFP growth rates across farm sizes to gain insight into whether observed productivity differences are likely to persist. The finding of a strong positive relationship between farm size and TFP suggests that consolidation of production has contributed to recent aggregate productivity growth in the crop sector. The study estimates the extent to which sectoral productivity growth can be attributed to structural change versus other factors including technological change. The study also explores some tradeoffs associated with policies that raise the productivity of small versus large farms.